Investigation of design space for freeze-drying injectable ibuprofen using response surface methodology - Preskar Maja; Videc Danijel; Vrečer Franc; Gašperlin Mirjana (Acta Pharmaceutica)
This study explores the use of a statistical model to build a design space for freeze-drying two formulations with ibuprofen. A 2 × 3 factorial experimental design was used to evaluate independent variables (filling volume and annealing time) and responses as residual moisture content, specific surface area and reconstitution time. A statistical model and response surface plots were generated to define the interactions among the selected variables. The models constructed for both formulations suggest that 1 mL of filled volume and no annealing should be used to achieve optimal residual moisture content, specific surface area and reconstitution time. The proposed models were validated with additional experiments, in which the responses observed were mainly in close agreement with the predicted ones. Additionally, the established models demonstrate the reliability of the evaluation procedure in predicting the selected responses.